Experimental Vibration Analysis for Civil Structures: Testing, Sensing, Monitoring, and Control - Zhang, Jian; Wu, Zhishen; Noori, Mohammad; Li, Yong (Resilience and Sustainability in Civil, Mechanical, Aerospace and Manufacturing Engineering Systems, 2020)
This book which contains contributions from leading researchers in the field of experimental vibration analysis for structural systems covers the latest developments in dynamic response and safety evaluation of civil structures. The topics covered include the state-of-art research in (1) damage identification and structural health monitoring, (2) testing, sensing, and analytical modeling, (3) vibration and seismic isolation, mitigation and control, (4) system and model identification utilizing the emerging computational and analytical tools, (5) coupled and complex systems such as human–structure, vehicle–structure, and soil–structure interaction and their impact on structural safety and reliability, and (6) application of big data and artificial intelligence (AI) techniques for dynamic response evaluation or fault detection in civil structures. This book intends to provide the latest developments in the aforementioned areas in order to better understand how to assess the state of health of structural, geo-structural, and complex infrastructure systems and how to predict their remaining useful life using the latest methodologies and tools in vibration analysis. A major focus is on understanding vibration data collected from these systems when subjected to operational and extreme loads. This is also the first book on this subject that presents the importance of advanced data analytics and AI based for damage identification and response prediction of critical infrastructure. This is a rapidly emerging field that can most effectively support decision making related to maintenance and inspection, retrofit, upgrade, and rehabilitation of critical infrastructure systems especially in case of emergency response. The contributions, presented in this book, can provide strategic roadmaps for research in the area of experimental vibration analysis for civil engineering structures and for building more resilient and sustainable civil infrastructure systems. Experimental Vibration Analysis for Civil Structures: Testing, Sensing, Monitoring, and Control covers a wide range of topics in the areas of vibration testing, instrumentation, and analysis of civil engineering and critical infrastructure. It explains how recent research, development, and applications in experimental vibration analysis of civil engineering structures have progressed significantly due to advancements in the fields of sensor and testing technologies, instrumentation, data acquisition systems, computer technology, computational modeling, and simulation of large and complex civil infrastructure systems. The book also examines how cutting-edge AI and data analytics can be applied to infrastructure systems. Features: Explains how recent technological developments have resulted in addressing the challenge of designing more resilient infrastructures Examines numerous research studies conducted by leading scholars in the field of infrastructure systems and civil engineering Presents the most emergent fields of civil engineering design, such as data analytics and AI for the analysis and performance assessment of infrastructure systems and their resilience Emphasizes the importance of an interdisciplinary approach to develop the modeling, analysis, and experimental tools for designing more resilient and intelligent infrastructures. Appropriate for practicing engineers and upper-level students, Experimental Vibration Analysis for Civil Structures: Testing, Sensing, Monitoring, and Control serves as a strategic roadmap for further research in the field of vibration testing and instrumentation of infrastructure systems.